«Կիլիկյան» կարծեցյալ նորահայտ երկու թերթերի մասին - Ենոքյան, Անի
An article about “newly discovered” Cilician manuscript folios recently appeared in the Պատմություն և մշակույթ (History and Culture) 18, a journal published by Yerevan State University. The article focuses on two folios from the private collection of Guillaume Aral19 in France. The author states that the style and iconography of the illustrations are related to the Cilician royal manuscripts, therefore, she concludes that the two folios are from a splendid Cilician royal manuscript, presumably created by a disciple or assistant of the outstanding miniaturist Sargis Pitsak in Sis.
Keywords: Մամուլ; Բանավեճեր